2014
DOI: 10.1002/2013ms000294
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control of tropical cyclones in CMIP5: A ventilation perspective

Abstract: The ventilation index serves as a theoretically based metric to assess possible changes in the statistics of tropical cyclones to combined changes in vertical wind shear, midlevel entropy deficit, and potential intensity in climate models. Model output from eight Coupled Model Intercomparison Project 5 models is used to calculate the ventilation index. The ventilation index and its relationship to tropical cyclone activity between two 20 year periods are compared: the historical experiment from 1981 to 2000 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 80 publications
(91 reference statements)
2
41
0
Order By: Relevance
“…Interestingly, Tang and Camargo [2014] showed that the ventilation index changes are consistent with changes in TC frequency in the CMIP5 models.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 75%
“…Interestingly, Tang and Camargo [2014] showed that the ventilation index changes are consistent with changes in TC frequency in the CMIP5 models.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 75%
“…A potential limitation of the GPI methodology for application to a different climate is that it is trained on presentday climate. This was demonstrated in the 25-km version of the CAM5 GCM, where decreases in GPI estimated for the 2CO2 experiment were consistent with the direct simulation but increases in GPI estimated for the 2K and 2K2CO2 experiments were inconsistent with the direct simulation of changes in tropical cyclone numbers (Wehner et al 2015; see also Camargo 2013; Camargo et al 2014). …”
mentioning
confidence: 86%
“…Zhao et al (2013a,b) This relationship between TC frequency and vertical velocity was the closest association found among a suite of analyzed variables that included precipitation, 600-hPa relative humidity, and vertical wind shear. In addition, Camargo et al (2014) use a number of GPIs applied to the output of the GFDL HiRAM to show that in order to explain the reduction in TC frequency, it is necessary to include saturation deficit and potential intensity in the genesis potential index. While the response of the models in the other HWG experiments is more ambiguous, no model generated a substantial increase in global TC frequency for any experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another large-scale environmental factor that should be considered is the ventilation, the import of cooler and drier air, which was shown to have an important influence in both tropical cyclogenesis and intensification (Tang and Emanuel 2012). Changes in TC frequency in future climates have also been related to the ventilation index for the CMIP5 models (Tang and Camargo 2014).…”
Section: June 2015 |mentioning
confidence: 99%